Safety, Efficacy, and Feasibility of Nebulized Long-Acting Bronchodilators vs Short-Acting Bronchodilators in Hospitalized Patients With Acute Exacerbations of COPD - Rajiv Dhand, MD; Samuel Treat, MD; Jennifer Ferris, MSHS; Paul D. Terry, PhD; Tracy Walker, BA; Scott Elder, RRT; Daniel Church, RRT; Danielle Dennis, PharmD; Barbara Faircloth, PharmD; Gulsah Onar, MPH; R. Eric Heidel, PhD; Isaac Biney, MD; et al. (CHEST Pulmonary)
Background: Long-acting bronchodilators are preferred over short-acting bronchodilators in patients with stable COPD, but prospective studies are needed to determine the safety and efficacy of nebulized long-acting bronchodilators in hospitalized patients with exacerbations of COPD. Research Question: In hospitalized patients with exacerbations of COPD, is a combination of nebulized long-acting formoterol/revefenacin as safe and effective as the short-acting nebulized albuterol/ipratropium combination? Study Design and Methods: We conducted a prospective, randomized, parallel-group study comparing a nebulized formoterol/revefenacin combination with an albuterol/ipratropium combination among 60 hospitalized patients (30 in each group) with exacerbations of COPD who tested negative for COVID-19. Treatments were administered every 12 to 24 hours (formoterol/revefenacin) or every 6 hours (albuterol/ipratropium) by jet nebulizers for up to 7 days. Safety and efficacy assessments were recorded on days 1, 3, and 7, or at hospital discharge. Assessment of dyspnea by the Modified Borg dyspnea scale was the primary outcome. Data were analyzed with parametric or nonparametric statistical tests, and generalized estimating equations with an identity link function were used to analyze differences in the two groups. Statistical significance was assumed at an unadjusted two-sided alpha value of 0.05. Results: Participants’ mean age was 63.2 (SD, 9.30) years, and 39 (65.0%) reported active tobacco use. Patients’ age, sex, race, smoking history, BMI, Charlson Comorbidity Index scores, supplemental oxygen requirements, and length of hospital stay were similar in the two groups (P > .05 for all). Patients receiving formoterol/revefenacin had similar Modified Borg dyspnea scores (P = .95) and required fewer total drug doses (P < .001), but there was a nonsignificant trend for more frequent rescue treatments (P = .08) compared with those receiving albuterol/ipratropium. There were no serious adverse events or treatment failures in either group. Interpretation: Our findings indicate that in nonventilated hospitalized patients with exacerbations of COPD, the institution of nebulized formoterol/revefenacin in combination within 24 to 36 hours of hospital admission provided convenient dosing and required fewer drug doses to achieve comparable efficacy and safety with the standard short-acting nebulized albuterol/ipratropium combination.